2019
DOI: 10.2134/jeq2018.08.0308
|View full text |Cite
|
Sign up to set email alerts
|

Gypsum Amendment Reduces Redox‐Induced Phosphorous Release from Freshly Manured, Flooded Soils to Floodwater

Abstract: The effectiveness of gypsum in reducing runoff P losses from soils and the mechanisms responsible are well documented; however, gypsum amendment effects in reducing redox‐induced P losses from flooded soils are less researched and documented. We examined the effect of gypsum amendment on P release from freshly manured soils to pore water and floodwater with continuous flooding for 56 d in the laboratory. Three soils (Pembina, Denham, and Dencross series) collected from Manitoba, Canada, were preincubated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 58 publications
4
14
1
Order By: Relevance
“…Similar trends in Eh values in response to flooding conditions have been previously reported, where flooding under warmer temperatures resulted in a more dramatic decrease in Eh, whereas flooding under colder temperatures resulted in a marginal decrease in Eh (Dharmakeerthi, Kumaragamage, Indraratne, & Goltz, 2019; Kumaragamage et al., 2020). In these previous studies with packed soil columns, Eh values under both warm and cold flooding were similar and somewhat stable during the initial stages of flooding up to about 21 DAF, but thereafter Eh values sharply declined under warm‐temperature flooding (Dharmakeerthi, Kumaragamage, Indraratne, & Goltz, 2019; Kumaragamage et al., 2020). In contrast, with intact soil monoliths in the current study, a sharp decline in Eh was observed immediately after flooding (within the first 14 DAF) in seven out of eight soils under warm temperatures (SSF) (Supplemental Figure S1).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Similar trends in Eh values in response to flooding conditions have been previously reported, where flooding under warmer temperatures resulted in a more dramatic decrease in Eh, whereas flooding under colder temperatures resulted in a marginal decrease in Eh (Dharmakeerthi, Kumaragamage, Indraratne, & Goltz, 2019; Kumaragamage et al., 2020). In these previous studies with packed soil columns, Eh values under both warm and cold flooding were similar and somewhat stable during the initial stages of flooding up to about 21 DAF, but thereafter Eh values sharply declined under warm‐temperature flooding (Dharmakeerthi, Kumaragamage, Indraratne, & Goltz, 2019; Kumaragamage et al., 2020). In contrast, with intact soil monoliths in the current study, a sharp decline in Eh was observed immediately after flooding (within the first 14 DAF) in seven out of eight soils under warm temperatures (SSF) (Supplemental Figure S1).…”
Section: Resultssupporting
confidence: 84%
“…The release of P from flooded soils is governed by temperature‐dependent multiple biogeochemical processes and their interactions (Amarawansha et al., 2015; Maranguit, Guillaume, & Kuzyakov, 2017; Rakotoson, Rabeharisoa, & Smolders, 2016). However, the majority of studies investigating the effects of flooding on P release from soils were conducted under room temperature or summer conditions (Amarawansha et al., 2015; Dharmakeerthi, Kumaragamage, Indraratne, & Goltz, 2019; Kumaragamage et al., 2020). A few studies investigating the temperature effect on flooding‐induced P release have shown that the rate and magnitude of P mobilization was greater when soils were flooded under warm than under cold temperatures (Dharmakeerthi, Kumaragamage, Goltz, & Indraratne, 2019; Kumaragamage et al., 2020; Tang et al., 2016), with an average Q 10 (temperature coefficient indicating the rate of change of a biological or a chemical system when temperature is increased by 10 °C) of around 2.8 when temperature was raised from 8 to 18 °C (Tang et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the concentration gradient of DRP between the pore water and floodwater is much higher in the sandy loam than in the clay in the current study. All these factors may explain the higher rate of P flux in the sandy loam, as previously observed in soils with contrasting textures (Dharmakeerthi et al, 2019b). This resulted in a decrease in pore water DRP concentration in the sandy loam, particularly in the unamended and biochar‐amended treatments under warm conditions beyond 4 WAF.…”
Section: Discussionsupporting
confidence: 64%
“…Floodwater DRP increased with flooding time under all experimental conditions as a result of effective diffusion of DRP from pore water to surface water (Jayarathne et al, 2016; Dharmakeerthi et al, 2019b). The rate of increase in floodwater DRP is faster under warm than cold conditions and in the sandy loam than in the clay.…”
Section: Discussionmentioning
confidence: 96%
“…Most of the documented evidence on enhanced P release from soils to floodwater has focused on summer flooding conditions and/or flooding under room temperatures (Amarawansha et al., 2015; Dharmakeerthi, Kumaragamage, Indraratne, & Goltz, 2019b; Tian et al., 2017). The magnitudes of P release from flooded soils under spring snowmelt conditions or cold temperatures are poorly represented in the literature (King et al., 2015).…”
Section: Introductionmentioning
confidence: 99%